A Case Report Of COVID-19 Re-Infection - Muhammad Imran Hasan Khan , Tayyaba Shaheen , Tanzeelah Shamshad, (Journal of Rawalpindi Medical College, 2021)
Spectrum of coronavirus disease continues to unfold as time passes. It has created health and economic crisis all over the world. Being a new virus, means less information on behavior and a lot to learn for its immunity. It was assumed initially that reinfection was less likely. Once exposed, we will develop antibodies and will be safe. But now we have a case of Covid-19 reinfection, depicting that despite of exposure and having IgG Antibody titer, reinfection occurred within 6 months.